Temporary work : an enabler for boundaryless careers ? - Alain LACROUX (Revue de Gestion des Ressources Humaines, 2009)
The aim of the present paper is to examinate the notion of career applied to the temporary help service (THS) workers. During the recent period, leader firms in the temporary help service industry in France are trying to build real “careers” for their temporary employees, by using various methods, such as enabling long term employment relationships, or making efforts to extend some benefits of the “permanents” employees to the temporary workers (mutual funds, occupational training…). Our ambition is to study the impacts of these evolutions on the temporary employees, by using the framework of the boundaryless careers [ex: Arthur and Rousseau – on 1996; Cadin and al – on 2003]. We formulate the hypothesis that the professional course of some specific temporary workers (mobile and qualified) can now be viewed as a real careers, regarding the framework proposed by the boundaryless careers theorists. To validate this hypothesis, we led a qualitative empirical study (31 interviews conducted with temporary work agency managers), completed by a questionnaire administered to a sample of 208 temporary employees.